Rapid quantification of the adulteration of fresh coconut water by dilution and sugars using Raman spectroscopy and chemometrics. (30th January 2019) - Richardson, Paul I.C.; Muhamadali, Howbeer; Ellis, David I.; Goodacre, Royston
Highlights: Raman spectroscopy was developed for the first time to detect adulteration in coconut water. Adulteration with water, single sugars, mixtures of sugars and HFCS were investigated. Spectra showed concentration-based quantification of dilution and masking by adulteration with single sugars. Small abnormalities in sugar ratios in coconut water could be discerned. Raman spectroscopy has potential for rapid on-site detection of adulteration in this product. Abstract: Here, for the first time, we developed Raman spectroscopy in combination with chemometrics for the quantification of adulteration of fresh coconut water by dilution, and its masking with sugars. Coconut water was extracted from young Costa Rican coconuts and heat treated to emulate pasteurization. Samples were then adulterated by dilution with water and single sugars, mixtures of sugars, and high-fructose corn syrup (HFCS). A total of 155 samples were analysed with Raman spectroscopy at 785 nm excitation and 620 spectra analysed with chemometrics. Results showed successful quantification of dilution and adulteration with single sugars between 1.9 and 2.6%, masking of dilution with mixtures of sugars at 9.8%, and masking of dilution with HFCS at 7.1%. It can be concluded that Raman spectroscopy has significant potential as a rapid accurate analytical method for the detection of adulteration in this product, with the ability to discern small abnormalities in sugar ratios within coconut water.